Pengaruh Self-Regulated Learning terhadap Hasil Belajar Geografi dengan Observasi Sebaya sebagai Moderator - Putri Irwan, Safana; Rery Novio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the suboptimal level of students' self-regulated learning (SRL), which affects geography learning outcomes. The purpose of this study is to analyze the effect of self-regulated learning on geography learning outcomes and to examine whether peer observation acts as a moderating variable. This study uses a quantitative method with a causal approach and a non-experimental design. The sample consists of 30 tenth-grade students of MAN 1 Kampar selected using purposive sampling. Data were collected through SRL questionnaires, geography learning outcome tests, and peer observation sheets. Data analysis was conducted using simple linear regression and moderated regression analysis. The results show that self-regulated learning affects students' geography learning outcomes. However, peer observation does not significantly moderate the relationship. In conclusion, SRL is the main factor influencing learning outcomes, while peer observation has not been proven as a moderating variable.